VET workers’ problem-solving skills in technology-rich environments: European approach - Hämäläinen, Raija; Cincinnato, Sebastiano; Malin, Antero; De Wever, Bram (International Journal for Research in Vocational Education and Training, 2014)
The European workplace is challenging VET adults’ problem-solving skills in technology-rich environments (TREs). So far, no international large-scale assessment data has been available for VET. The PIAAC data comprise the most comprehensive source of information on adults’ skills to date. The present study (N=50 369) focuses on gaining insight into the problem-solving skills in TREs of adults with a VET background. When examining the similarities and differences in VET adults’ problem-solving skills in TREs across 11 European countries, two main trends can be observed. First, our results show that only a minority of VET adults perform at a high level. Second, there seems to be substantial variation between countries with respect to the proportion of VET adults that can be identified as “at-risk” or “weak” performers. For the future, our findings indicate the variations that can be used as a starting point to identify beneficial VET approaches.